Lancaster County (Pa.) ledger
Ledger kept by an unidentified Lancaster County , Pennsylvania, storekeeper.
Collection material in English
Keywords: Merchants -- Pennsylvania -- Lancaster County; Lancaster County (Pa.) -- Commerce